Efficacy of Homoeopathic Medicine in Obsessive Compulsive Disorder (Homoeopathy for All, 2025)
OCD is the mental disorder with fear & anxiety accompanied with compulsive behaviour & thoughts.
Keywords: Obsessive compulsive disorder; Mental symptoms